Transcatheter patent ductus arteriosus closure with echocardiographic guidance: can radiation exposure be reduced? - İbrahim Cansaran Tanıdır; Alper Guzeltas; Yakup Ergul; Erkut Ozturk; Isa Ozyilmaz; Ender Odemis (KARE Publishing, 2014)
Objectives: The radiation dose from interventional cardiac catheterization is particularly relevant when treating children because of their greater radiosensitivity compared to adults. The transcatheter closure of patent ductus arteriosus (PDA), as well as other more complex pediatric interventions, have raised concerns regarding radiation exposure, particularly relevant when treating children. The purpose of this study is to show how to perform the transcatheter closure of PDA in children while giving less ionized radiation and to prove that the amount of radiation and contrast material can be reduced. Study design: Following appropriate device selection based on PDA morphology and diameter, transthorasic echocardiography images and control aortography findings were analyzed. The following devices were used during the procedure: Gianturco coils (10/63), an Amplatzer Duct Occluder (ADO, 31/63), Flipper coils (19/63), and an Amplatzer vascular plug (3/63). Results: The scopy time, radiation dose, and contrast were 12+-6.4 mins, 28.1+-14.7 cmGy/cm2/kg, and 4.2 +- 2.3 cc/ kg, respectively. In the control aortography shortly after the procedure, residual shunt was detected at various levels in 39.7% of patients, and 9.5% demonstrated residual shunt in real-time echocardiography. In the control aortography, the exposure to radiation was 13.3% of the total, and the amount of infused contrast was 27.2% of the total. Conclusion: Patients may be exposed to less radiation and contrast material if an echocardiographic evaluation, instead of a final control aortography injection, is performed after the transcatheter closure of PDA.